Standards of textuality in perfume and cosmetic names - Nikiforova, Yevgeniia; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2020)
This article deals with the problem of perfume and cosmetic names. Special attention is given to the peculiarities of names in the context of textuality. Perfume and cosmetic names verbalize all features, qualities and individual characteristics of these goods. They create the naming space that consists of four nominative components: brand, basic, genitive and functional-descriptive. It is the basic nominative component that reflects the main part of information about perfumes and cosmetic goods. Four nominative components function as corresponding text information blocks. It means that perfume and cosmetic name combines two spaces. The first space is naming that is represented with the integrated perfume and cosmetic naming complex. The complex grasps four nominative components. The second space is informational that stores the necessary volume of information and creates a communicative background. The information scope is kept in the text construction. The volume of information is divided into four relevant text blocks. Together all these blocks form text boundaries which outline the text construction. The text construction is characterized by two interdependent features coexisting in the integrated perfume and cosmetic naming complex such as discreteness and wholeness. This is a very significant cohesive factor within the text construction. Cohesion is realized on the lexical level involving the mechanism of repetition which is the part of reiteration. On the other hand, repetition may be complete (the naming unit is repeated literally) and partial (the naming unit is repeated partly). The repetition may be between nearest blocks (having common side) and distant blocks (without a common side). The result of the research broadens the set of naming units adding to word, phrase and sentence the next unit recognized as text.
Keywords: cohesion, lexical repetition, naming complex, nominative component, text block, text construction.